Efficiency performance of Malaysian listed Government Linked Companies (GLCs) : A Stochastic Frontier Analysis/ Norhana Salamudin, Rosita Suhaimi & Jennifer Tunga Janang - Salamudin, Norhana; Suhaimi, Rosita; Janang, Jennifer Tunga (2011)
The creation of government linked companies (GLCs) started when the Malaysian government implemented its privatization programme in the 1980s. The privatization policy includes many privatization techniques, amongst them, is the transfer of former state owned enterprises (SOEs) to private ownership and to participate in profit oriented business concern. As private transfers are minimal and equity ownership is still largely in the hand ofthe state, these privatized firms are often known as government linked companies.